Socioeconomic Dynamics of Poverty in Senegal: A Comprehensive Analysis - Haben Delio (International Journal of Science and Society, 2023)
This scholarly journal article delves into the multifaceted issue of poverty in Senegal, a West African country with a rich cultural heritage and diverse population. Poverty remains a significant challenge that hampers the country's development efforts and the well-being of its citizens. The purpose of this study is to provide a comprehensive analysis of the socioeconomic dynamics contributing to poverty in Senegal, examining its root causes, manifestations, and potential solutions.